Discourse in Action - Jones, Rodney H (Taylor & Francis, 2005)
From emails relating to adoption over the Internet to discussions in the airline cockpit, the spoken or written texts we produce can have significant social consequences. The area of Mediated Discourse Analysis considers texts in their social and cultural contexts to explore the actions individuals take with texts - and the consequences of those actions. Discourse in Action: brings together leading scholars from around the world in the area of Mediated Discourse Analysis reveals ways in which its theory and methodology can be used in research into contemporary social situations explores real situations and draws on real data in each chapter shows how analysis of texts in their social contexts broadens our understanding of the real world. Taken together, the chapters provide a comprehensive overview to the field and present a range of current studies that address some of the most important questions facing students and researchers in linguistics, education, communication studies and other fields.